Social perception of childhood overweight and obesity to generate prevention strategies in Nuevo Leon, Mexico - Garcia, Janet; Picazzo-Palencia, Esteban; Cortes-Hernández, Dora Elia; Silva-Aguilar, Kabáh (Horizonte Sanitario, 2015)
Objective . To determine the social perception on childhood overweight and obesity for the purpose of generating communication strategies that would prevent it through changes in behavior. Materials and methods : A descriptive study using a qualitative research method that involved focus groups with children, teachers and parents. The type of analysis was argumentative. The study was conducted from January to May 2013 in the metropolitan area of Monterrey, Nuevo León, Mexico. Results : There is a most diffrent social perception among focus groups on the quality of life and happiness of children, with parents and teachers referring to food in relation to children happiness when it is provided as a reward or to compensate for bad experiences or lack of emotional attachment, while children refer to family harmony as the main cause for making them happy. Conclusions : The social perception reveals the importance of social or symbolic interaction processes. Therefore, the objective of the communication strategy must address the associated factors in preventing obesity through symbolic elements of these groups, taking into account the senses and meanings related to basic stimuli that trigger behaviors related to obesity